Frugal Innovation in Education: Designing and Evaluating Low-Bandwidth, Asynchronous Learning Systems for Remote Indonesian Schools - Hesti Putri; Maya Enderson; Jasmila Tanjung; Matilda Munoz; Sarah Armalia; Jovanka Andina; Kevin Setiawan; Sudarto Sudarto; Khalil Jibran; Jasmine Alieva (Enigma in Education, 2025)
The promise of educational technology (EdTech) to democratize learning in Indonesia is consistently undermined by a profound digital divide, particularly in remote and archipelagic regions where internet connectivity is poor and infrastructure is limited. This study explores the application of frugal innovation principles as a direct and context-aware strategy to address this challenge. A multi-phase, mixed-methods Design-Based Research (DBR) methodology was employed over 18 months. The study involved the collaborative design, development, and implementation of "Lentera," a low-bandwidth, asynchronous, and offline-first learning system, in six remote primary schools in the Maluku Islands. A quasi-experimental design compared three intervention schools with three control schools over one academic year. Data collection was extensive, including pre- and post-intervention literacy and numeracy assessments, System Usability Scale (SUS) surveys, system usage logs, semi-structured interviews with 18 teachers, and over 80 hours of classroom observation. Data were analyzed using a two-level Hierarchical Linear Model (HLM) to account for the clustered nature of students within schools. The Lentera system demonstrated high feasibility and positive user adoption, with offline peer-to-peer sharing proving to be a critical feature for content distribution. Quantitative analysis revealed a statistically significant and substantial improvement in learning outcomes for the intervention group in both literacy (γ = 11.85, p < 0.001) and numeracy (γ = 12.91, p < 0.001) compared to the control group, after controlling for pre-test scores. The mean System Usability Scale (SUS) score was 78.5, indicating well-above-average usability. Qualitative findings, drawn from a wide range of teacher interviews and classroom observations, highlighted the system's effectiveness in supporting student-centered, differentiated instruction and fostering teacher collaboration, aligning with the core principles of Indonesia's Kurikulum Merdeka. The study provides compelling evidence that frugal innovation, embodied in a context-aware learning system, presents a viable, effective, and scalable pathway to enhancing educational quality and equity in resource-constrained environments.